Regional Differences in the Components of Luminal Water from Rat Gastrointestinal Tract and Comparison with Other Species. - Yusuke Tanaka; Toshihiro Hara; Ryoichi Waki; Shunji Nagata (Frontiers Media S.A., 2012)
Purpose. The bile acids, phospholipids, inorganic ions, and pH in luminal fluid are very important factors for the dissolution and oral absorption of solid drugs. In this study, we evaluated the regional differences in these factors in the rat GI tract. The solubility of griseofulvin, a poorly water-soluble drug, in the luminal fluid in each segment was also measured. In addition, the data from rats were compared with those from other species published previously to evaluate the species differences in the composition of luminal fluid. Methods. Rat abdomen was opened and residual water was sampled from each region of GI tract to measure the various components concentrations. Results. The total bile acid and phospholipid concentrations were much higher in the lower jejunum and upper jejunum, respectively, than in the other regions. The solubilities of griseofulvin in the lower jejunal fluid (153-260 g/mL) were about 1.5-2 times higher than those in the upper jejunal fluid (99-146 g/mL). The regional differences in inorganic ions and pH were also observed. As for species differences, the total bile acid and phospholipid concentration in rats GI tract were much higher than those of dogs and humans. Conclusion. These informations about the regional differences and species differences of the components in the GI fluid should be very useful to consider dissolution and oral absorption of solid drugs.